Influence of cranium orientation on cervical sagittal alignment during radiographic examination: a radiographic analysis - Miyake, Katsuhiro; Fujishiro, Takashi; Yamamoto, Yuki; Usami, Yoshitada; Hayama, Sachio; Nakaya, Yoshiharu; Neo, Masashi (The spine journal, 2024)
During the radiographic examination, the cranium orientation varies not only individually but also within the same subject, in different imaging sessions. Knowing how changes in the orientation of the cranium influences cervical sagittal alignment during the radiographic examination of the cervical spine can aid clinicians in the accurate evaluation for cervical sagittal alignment in clinical practice. To radiographically examine the influence of cranium orientation on cervical sagittal alignment during radiographic examination in an asymptomatic cohort. A prospective radiographic study. Eighty asymptomatic volunteers (mean age, 40.4 years; 50.0% male) were enrolled. Cervical sagittal parameters including the regional slope (C1 slope, C2 slope, C5 slope, C7 slope, and T1 slope), Cobb angle (O–C1 angle, C1–C2 angle, C2–C5 angle, C5–C7 angle, and C7–T1 angle), and cranial/cervical offset (sella turcica tilt [ST tilt] and C2 tilt). In all participants, standing lateral radiographs of the cervical spine were taken in 3 forward-gazing positions: anteverted-cranium (AC) position; neutral-cranium (NC) position; and retroverted-cranium (RC) position. Cervical sagittal parameters, including the regional slope, Cobb angle, and cranial/cervical offset, in these 3 positions were statistically compared. The C1 and C2 slopes were anteverted and retroverted in the AC and RC positions, respectively, compared to those in the NC position. The C5 slope, C7 slope, and T1 slope were constant among the 3 positions. In O–C2 and C2–C5, statistically significant differences in the regional Cobb angles were identified among the 3 positions; however, there were no significant differences in the C5–C7 or C7–T1 segments. Cranial and cervical offsets of ST tilt and C2 tilt increased and decreased when the cranium was anteverted and retroverted, respectively. The current study suggests that the adjustment of the cranium orientation when taking cervical spine radiographs is mainly controlled at the upper cervical spine of the O–C2 segment in an asymptomatic cohort. On radiograph, alignment in the upper cervical segment of O–C2 changes; accordingly, the middle cervical segment of C2–C5 can change during the adjustment of cranium orientation. However, alignment in the lower cervical segment of C5–C7 and the cervicothoracic junction of C7–T1 remains constant. Further, cranial/cervical offset increases and decreases when the cranium is anteverted and retroverted, respectively. Our results can help the accurate evaluation of cervical sagittal alignment on plain radiographs in clinical practice.